Communications and Learning Behaviour: Selected References - Penland, Patrick R. (Journal of Information and Knowledge, 1977)
This is a list of references on Communication and Learning Behaviour. Most of these references are cited in Papers B to E of this Volume. The Citations are indicated by the name of the author and the year of publication of the document. The citations are in parenthesis.